Contemporary piracy and maritime terrorism the threat to international security - Murphy, Martin N. (Adelphi papers, 2007)
Do piracy and maritime terrorism, individually or together, present a threat to international security, and what relationship if any exists between them? Piracy may be a marginal problem in itself, but the connections between organised piracy and wider criminal networks and corruption on land make it an element of a phenomenon that can have a weakening effect on states and a destabilising one on the regions in which it is found. Furthermore, it is also an aspect of a broader problem of disorder at sea that, exacerbated by the increasing pressure on littoral waters from growing numbe